FEATURES OF HYDROGEOLOGICAL AND THERMOBARIC CONDITIONS OF THE VLACHIVSKE OIL AND GAS CONDENSATE FIELD - NIMETS, Olexandr; NIMETS, Dmytro; CHOMKO, Dmytro; UDALOV, Igor (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
Background. Today, the practical tasks of oil and gas geology include prospecting and exploration, subsoil development, development of oil and gas fields and many others related to a wide range of related sciences, such as anthropogenic impact on the geological environment, environmental and hydrogeological issues of the impact of oil and gas fields on drinking water, etc. This paper deals with the hydrogeological and thermobaric conditions of the Valyukhivske oil and gas condensate field (OGCF), which is located in the junction zone of the northern coastal zone and the central axial zone of the Dnipro-Donetsk Basin (DDB). Methods. The proposed methodological approach is based on the theoretical notion that regional geothermal anomalies can be formed only by hydrocarbon (methane) gases due to their vertical migration. Therefore, the priority is to search for areas within oil and gas basins that are characterised by elevated geothermal field values as a result of certain factors (neotectonic movements, etc.). At the next stage, the hydrogeological conditions of the section are determined, and their relationship with the oil and gas content of the region is investigated. Subsequently, the gas- geochemical conditions of the section are determined, and the relationship of the component composition of free gases with depth and current reservoir temperatures is established. Results. The Valiikhvske OGCF is interesting in hydrogeological terms because in its section within the lower hydrogeological floor a thermo- dehydration hydrogeological zone and related phenomena, such as abnormally high reservoir pressures, are developing. In addition, the thermo- dehydration zone here is not only a huge area of hydrocarbon migration, but also contains their commercial accumulations in the sediments of the Tournai and Famenian stages. Сonclusions. Based on the analysis, it was found that the catagenetic fluidic stop (CFS) in the field section lies in the depth range of 4.6–5.0 km and has heterogeneity of the lower hydrogeological floor, two hydrogeological zones were identified. The upper one is elision zone, which is widespread in the section above the CFC, and the lower one is thermo-dehydration zone, which becomes extensive in the section below the CFC. The productive horizons of the Valyukhivske OGCF are known both within the EGD and TDGD. Taking into account the data obtained, we can state that the geological setting of the deep horizons of the Valyukhivske OGCF field contributes not only to the vertical migration of HC within the TDGF, but also to their accumulation on an industrial scale.